Evoked potentials - Shkurovich Z., Mario; Collado C., Miguel Ángel; Reyes, Bartolo (Revista Mexicana de Ingenieria Biomedica, 1991)
The evoked or evoked potentials (PE) are the respective cerebral electrical response, as well as some specific spinal or subcortical relays, before the application of a stimulus that can be auditory (click, pips, burst, etc.), electrical, visual (light flash, chromatic pattern on TV etc.), pressure, etc. which are extracted from the background electroencephalogram (EEG) with analog-digital-digital-analogue averaging technique (AD-DA).